IMPACT OF AQUAPORIN-3, AQUAPORIN-7 AND HEPARANASE GENETIC POLYMORPHISMS ON AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE PROGRESSION. (June 2022) - Santos, Ana Carolina; Rechitean, Andreea; Silva, Inês Vieira Da; Matos, Andreia; Ferreira, Joana; Soveral, Graça; Bicho, Manuel; Almeida, Edgar
Abstract : Objective: Autosomal Dominant Polycystic Kidney Disease(ADPKD) is a monogenic disease characterized by the growth of cysts in the kidneys, which can progress to end-stage renal disease(ESRD). However, this progression is heterogeneous. Aquaporin-3(AQP3) and Aquaporin-7(AQP7) are water channels involved in the inflammatory response and proliferation, expressed in the kidney and may have a role in cyst epithelial proliferation. Heparanase(HPSE) is an enzyme that cleaves heparan sulfate side chains of proteoglycans and has an increased expression in the glomerulus in diseases associated with proteinuria. This study aims to evaluate the impact of AQP3, AQP7 and HPSE genetic polymorphisms and some biomarkers related to cardiovascular risk in ESRD progression in patients with ADPKD. Design and method: 95 ADPKD(52.6% females), mean age 44.78 ± 14.34 years were diagnosed and had follow-up> 60 months. Variation values of serum creatinine(SCr) were used to stratify patients into fast progressors(FP) and slow progressors. Biochemical parameters and genetic polymorphisms were determined by standardized methods and endpoint analysis, respectively. Statistical analysis was performed using SPSS software considering p-value < 0.05. Results: For HPSE, genotype AA was associated with increased risk for FP in CKD(p = 0.027), while allele G was associated with high values of SCr(p = 0.010). A trend was observed in genotype CC of AQP7 with higher SCr(p = 0.066). No associations were found between AQP3 polymorphism and progression in ADPKD. The increased levels of: creatinine(SCr), albumin creatinine ratio(Alb/Cr), microalbumin(mAlb) and parathyroid hormone(PTH) were associated with the FP and stage 4 and 5 of chronic kidney disease(CKD). The opposite occurred in hemoglobin(Hb) levels and the product of calcium and phosphorus. No associations were found between AQP3 polymorphism and progression in ADPKD. Higher values of SCr were found in genotype CC of AQP3(p = 0.016) and a trend in allele T of AQP7(p = 0.070) and genotype AA of HPSE(p = 0.056). PTH was higher in genotype CC of AQP3(p = 0.047). AQP7 polymorphism was associated with elevated values of:Alb/Scr(p = 0.021) in allele T, calcium(p = 0.003) in genotype TT and Hb(p = 0.012) in allele C. Conclusions: The studied polymorphisms seem to directly impact and/or modulate levels of some biomarkers associated with progression and stage of CKD in ADPKD patients.